Addressing Low-Level Reproduction in Academic Publication: Implications for Integrity and Academic Environment - Zhu, Yi (IJRDO - Journal of Social Science and Humanities Research, 2023)
This paper addresses the issue of low-level reproduction in academic publication, which is considered a form of imperceptible academic corruption. The practice of low-level reproduction creates academic bubbles and undermines the integrity of the academic atmosphere. In response, this paper advocates for the banning of low-level reproduction to uphold the principles of scientific integrity within the scientific community. By doing so, it aims to foster an environment that nurtures critical thinking, creativity, and problem-solving skills among researchers, ultimately benefiting society and the nation as a whole. The paper emphasizes the importance of promoting transparent and original research in academic publishing to maintain the credibility and trustworthiness of scholarly work.